MODEL PENDEKATAN PSIKOLOGI DALAM STUDI ISLAM: ANALISIS TERHADAP METODE DAN APLIKASI PENGEMBANGANNYA - Dirmi, Dery Andika (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2024)
This study aims to explore the psychological approach model in Islamic studies. The study begins with the growing issues faced by humanity, particularly Muslims, in various aspects of life. The different approaches offered to address and follow up on these issues are felt to be insufficient and not professional enough to achieve their goals. There are three research questions in this study: First, what is the definition and historical development of the discipline of psychology? Second, how does psychology intersect with religion? Third, how is the psychological approach model applied in Islamic studies? The type of research used is qualitative research with a library research approach. The research findings indicate that the psychological approach is effective in addressing various issues within the scope of Islamic studies. Islamic psychology is a discipline that integrates psychological principles with Islamic spiritual values. This approach offers a systematic therapeutic framework based on Islamic sources, such as the Qur'an and Hadith. By studying mental phenomena, behavior, and values important for humanity, Islamic psychology contributes to the development of spirituality, well-being, and the resolution of religious issues. The object of the psychological approach itself is humans and their behavior. In Islamic psychology, the Qur'an, Hadith, and other Islamic sources can be used as references for study and as a return to address any issues that arise.